2014
DOI: 10.1038/ki.2013.339
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed soluble Fms–like tyrosine kinase-1 production aggravates atherosclerosis in chronic kidney disease

Abstract: Patients with chronic kidney disease (CKD) die of cardiovascular diseases for unknown reasons. Blood vessel formation in plaques and its relationship with plaque stability could be involved with signaling through the Flt-1 receptor and its ligands, vascular endothelial growth factor, and the closely related placental growth factor (PlGF). Flt-1 also exists as a circulating regulatory splice variant short-inhibitory form (sFlt-1) that serves as a decoy receptor, thereby inactivating PlGF. Heparin releases sFlt-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 41 publications
2
59
2
2
Order By: Relevance
“…20,21 In our previous study, MCP-1 mRNA was upregulated in peritoneal macrophages in sFlt-1 −/− mice. 4 Furthermore, the present study revealed that macrophages were skewed into the CD68 + CD206 − inflammatory phenotype, and that MCP-1 expression was significantly increased in the pressure-overloaded hearts of sFlt-1 −/− compared with the WT mice. On the basis of these findings, it is likely that MCP-1 acts downstream of PLGF/Flt-1 signaling.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…20,21 In our previous study, MCP-1 mRNA was upregulated in peritoneal macrophages in sFlt-1 −/− mice. 4 Furthermore, the present study revealed that macrophages were skewed into the CD68 + CD206 − inflammatory phenotype, and that MCP-1 expression was significantly increased in the pressure-overloaded hearts of sFlt-1 −/− compared with the WT mice. On the basis of these findings, it is likely that MCP-1 acts downstream of PLGF/Flt-1 signaling.…”
Section: Discussionmentioning
confidence: 74%
“…4,8,39 These findings indicate that postheparin sFlt-1 levels can be a surrogate marker for the total amount of sFlt-1 production. 4 We found that postheparin sFlt-1 levels are reduced by approximately half in dialysis patients compared with healthy subjects. 4 On the basis of these findings, we propose that the suppressed production of sFlt-1 exhibits one of the characteristics of CKD.…”
Section: 4mentioning
confidence: 86%
See 3 more Smart Citations